Sub-chronic treatment with high doses of ascorbic acid reduces lead levels in hen eggs intentionally exposed to a concentrated source of lead: a pilot study - Ramzi Shawahna; Ahed Zyoud; Elaf Haj Yahia; Rahma Sulieman; Abeer Haddad; Mohammad Makhlof; Bilal Abu-Hilal; Ghulam Murtaza; Hikmat Hilal (BMC, 2020)
Abstract Background Hen eggs contaminated with lead can be harmful to the health of children and adults. The objective of this pilot study was to investigate if sub-chronic treatment with ascorbic acid can reduce lead levels in the different parts of hen eggs after intentionally exposing the laying hens to a concentrated source of lead. Methods Clinically normal mixed-breed egg laying hens (n = 18) were used in this pilot study. Hens were exposed to a concentrated source of lead (200 mg/kgbody weight/day lead acetate) for 1 week. Subsequently, egg laying hens were either treated with sub-chronic doses of ascorbic acid (500 mg/kgbody weight/day) or left untreated for 4 weeks. Lead levels were assessed in egg-shell, egg-albumen, and egg-yolk samples using a graphite furnace atomic absorption spectrophotometer. Results Lead levels increased significantly (p-value < 0.01) from baseline in egg-yolk, egg-albumen, and egg-shell samples following 1 week exposure to lead acetate. Sub-chronic treatment of egg laying hens with high doses of ascorbic acid could bring statistically significant reduction (p-value < 0.01) in lead levels in egg-yolk, egg-albumen, and egg-shell samples after intentional exposure to a concentrated source of lead. Conclusions Findings of this pilot study showed that sub-chronic treatment of egg laying hens with ascorbic acid can reduce lead levels in different egg parts after intentional exposure to a concentrated source of lead. Supplementing feedstuffs and water with sources of ascorbic acid could be beneficial in reducing lead levels in hen egg tissues following environmental exposure. Further studies are still required to investigate if ascorbic acid can reduce lead levels in other chicken tissues.